The Nepenthes micramphora (Nepenthaceae) group, with two new species from Mindanao, Philippines - Cheek, Martin; Jebb, Matthew (Phytotaxa, 2013)
The N. micramphora group is erected to accommodate the species N. micramphora, N. abgracilis sp. nov. and N. cid sp. nov. from submontane habitats in Mindanao, Philippines. An overview of the genus in the Philippines is presented in the context of recent discoveries. The greater taxonomic importance of pitcher characters over those of the flowers in the genus is reviewed and hypotheses are provided to account for this phenomenon.